1986
DOI: 10.1203/00006450-198612000-00028
|View full text |Cite
|
Sign up to set email alerts
|

Transient Increase in Postnatal Testicular Activity Is Not Revealed by Longitudinal Measurements of Salivary Testosterone

Abstract: ABSTRACT. Testicular steroidogenic activity in 22 boys was monitored longitudinally over the first 6 months of life using salivary T measurements. Samples were collected biweekly. The highest T levels, 130 f 12 pmol/liter (mean f SE, n=22), were observed on days 2-10. The values then gradually declined to a mean of about 30 pmol/liter after month 4. No secondary peak in salivary T appeared, in contrast to the 1-3-month peak in serum T previously reported. The overall levels of T, reflected by the areas under t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 21 publications
3
16
0
Order By: Relevance
“…Our study confirms previous reports [1,2,9] where serum total T was found to be transiently elevated during the first postnatal months with peaks at 1-4 months. In contrast to previous studies [2,9,10], our study shows that salivary T levels in infants peak between 1 and 2 months when measured by LC-MS/MS, declining thereafter. Mean serum total T was higher in adolescents than in infants in our study, but there was no statistical difference between the 2 due to a small sample size.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study confirms previous reports [1,2,9] where serum total T was found to be transiently elevated during the first postnatal months with peaks at 1-4 months. In contrast to previous studies [2,9,10], our study shows that salivary T levels in infants peak between 1 and 2 months when measured by LC-MS/MS, declining thereafter. Mean serum total T was higher in adolescents than in infants in our study, but there was no statistical difference between the 2 due to a small sample size.…”
Section: Discussionsupporting
confidence: 93%
“…Huhtaniemi et al [9] and Cho et al [10] each measured salivary T using RIA during infancy. They reported contrasting results with peaks in salivary T at 7-10 days and 4 months, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tes tosterone produced during this interval may have low bioavailability owing to the rise in sex hormone binding globulin (SHBG) at this time (26)(27)(28). However, cellular level bioassay reveals biologically active androgens in male infants at 3 months of age (29).…”
Section: Normative Physiology Of Testosterone and Male Cns Developmenmentioning
confidence: 99%
“…In infant boys, serum testosterone levels increase to peak levels around 3 months of age and fall to prepubertal values around 6 months of age (Forest et al, 1974). Although levels of free testosterone in infancy are much lower than that in adulthood (de Ronde et al, 2005;Huhtaniemi et al, 1986), the postnatal increase in testosterone levels is critical for the normal development of male genitalia (Main et al, 2005) and higher postnatal salivary testosterone in boys predicts greater male-typical visual interests during early infancy (Alexander et al, 2009a). Significantly, the hypothesis that androgens levels in the early postnatal period may contribute to the organization of sex-linked behavior in humans (Alexander and Saenz, 2011;Alexander et al, 2009a) is supported by recent findings that postnatal urinary testosterone levels are associated with greater male-typical play behavior and less female-typical play behavior in girls and boys, respectively, at 14-months of age (Lamminmaki et al, 2012).…”
Section: Introductionmentioning
confidence: 99%